The impacts of industry 4.0 on the law and how can we respond to it - focusing on the employment law - LIN, Geng-Schen (Vietnam national university, Hanoi, 2020)
I. Introduction. II. Who is “employee”. III. Working time. IV. Workers’ participation. V. Strike